Report of the 5th International Congress of Tropical Animal Production 2015 - Díaz, María Felicia (Cuban Journal of Agricultural Science, 2016)
After 4 days of hard scientific work, we are gathered in plenary session for revealing the report of the 5th International Congress of Tropical Animal Production 2015. This event had an attendance of 465 participants from prestigious national and international scientific and teaching institutions, organizations, companies, associations, and national and international primary producers.